2022
DOI: 10.14201/fjc.28249
|View full text |Cite
|
Sign up to set email alerts
|

Divulgación científica en YouTube

Abstract: En los últimos años han ido emergiendo en YouTube divulgadores independientes de prácticamente la totalidad de campos académicos, culturales y científicos; también conocidos como influencers de ciencia. Paralelamente, las tradicionales instituciones académicas y científicas se han sumado al fenómeno de la divulgación digital lanzando sus propios canales de YouTube, como es el caso de las Unidades de Cultura Científica e Innovación (UCC+i) de la mayoría de universidades españolas. Este artículo profundiza en la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…1. Para dar respuesta al OE1 se adoptan métricas cuantitativas (Buitrago & Torres Ortiz, 2022;Yalamanchili et al, 2022): número de "me gusta", comentarios efectuados y número de seguidores.…”
Section: Metodologíaunclassified
“…1. Para dar respuesta al OE1 se adoptan métricas cuantitativas (Buitrago & Torres Ortiz, 2022;Yalamanchili et al, 2022): número de "me gusta", comentarios efectuados y número de seguidores.…”
Section: Metodologíaunclassified
“…These elements of the influencer's characterisation fall in line with Bandura's [27] contention that social modelling is most powerful when the hero character is socially attractive and relatable to the audience's demographics. Indeed, an analysis of YouTube videos by science institutions compared with those by science influencers showed that the latter produced far greater reach and engagement [79]. Science influencers can popularize and amplify science [80].…”
Section: Influencermentioning
confidence: 99%
“…Several studies indicate that content elicits the greatest level of interest when it is presented with humour and an air of novelty, as this awakens the audience's interest. This is why scientific institutions with a digital media strategy are still less relevant than content creators, as they have struggled to adapt to the language of social networks (Sidorenko-Bautista, Cabezuelo-Lorenzo and Herranz-de-la-Casa, 2021; Buitrago and Torres Ortiz, 2022). This adaptation to social media codes has generated large communities among content creators specialising in science.…”
Section: Social Network As a Channel For The Dissemination Of Sciencementioning
confidence: 99%